The Investigation of a Middle School Teacher Preparatory Program Through the Lens of Invitational Leadership - Price- Richardson, Christina L.; Martin, Barbara N. (Advances in Social Sciences Research Journal, 2022)
Using the principles and domains of invitational leadership identified by Purkey and Novak (2016), the researchers focused specifically on the inclusion of caring, respect, trust, optimism, and intentionality throughout the domains of people, places, policies, programs, and processes for creating an inviting culture in a teacher preparatory program. The results concluded the program was effective at including many of the principles through the domains of invitational leadership by role modeling, building relationships within the community of learners, and offering collaborative opportunities to the students. However, often this use was unintentionally inviting indicating that there was a need to further study invitational leadership theory to implement it effectively.